ANALISIS KETERAMPILAN MENULIS KARANGAN DESKRIPSI PADA SISWA KELAS IVB DI SD KARTIKA XVII-1 - Pilipus, Abilo Juan; Kartono, Kartono; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to analyze students' skills in writing descriptive essays. The research method is descriptive qualitative. The object of research is student essays which are assessed from the aspects of spelling usage and writing, word/diction writing, inter-sentence integration, inter-paragraph integration and overall content. Sources of data are students of class IVB SD Kartika XVII-1 Pontianak City, totaling 25 students. This research uses interview, test and documentation techniques. The results showed that the average descriptive essay writing skill was 56 in the (less) category. This can be seen in terms of the percentage of students getting scores in the very good category, none in the good category, 6 students or 0.24%, the enough category 6 students or 0.24%, the less category 13 students or 0.52%. Accuracy in writing descriptive essays has several aspects including the use and writing of spelling (use of capital letters, punctuation, writing less letters, hyphens), integration between paragraphs, and overall content. It can be concluded that the ability to write descriptive essays for class IVB students is included in the sufficient category because there are still some students who are less precise in writing descriptive essays